RELASI STRUKTUR MASYARAKAT DAN TATA ZONASI PERMUKIMAN ADAT DI DESA NGGELA, ENDE-FLORES - Fabiola T.A. Kerong (ATRIUM: Jurnal Arsitektur, 2015)
Title: Community Structure and Zone System Relationship of Nggela Traditional Settlement at Ende, Flores Nggela traditonal housing in one of the indigenous settlements that still persist authenticity in Ende-Flores. The traditional leaders who are members of a community structure still exist there and this indigenous settlements are divided into some districts. This study attempts to grasp the relationship between the community structure and zoning, furthermore are there other factors that influencing those relationship. This study applied qualitative methods with naturalistic approach. This study found that the community structure influence zoning system, together wioth other factors, like cosmology, history, protection, activities and sacred territory elements.